Customer Satisfaction and Logistics Company Reputation through Supply Chain Disruption Management - Saribanon, Euis; Simarmata, Juliater; Yuliantini, Yuliantini; Wardana, Aditya; Ramdhany, M.Arief (Jurnal Manajemen Pelayanan Publik, 2024)
Operations and supply chains of logistics companies can be disrupted by unplanned or unanticipated events. The purpose of this study is to determine the description of SCDM, customer satisfaction, and reputation of logistics companies in Jakarta, and to confirm the direct and indirect effects of SCDM on customer satisfaction and reputation of logistics companies in Jakarta. This research uses quantitative research methods. This study uses a questionnaire with a Likert scale with intervals of 1-9. Data were collected through questionnaires and analyzed using Partial Least Square (PLS). The findings of this study are (1) SCDM positively affects customer satisfaction; (2) SCDM affects corporate reputation directly and through customer satisfaction; and (3) customer satisfaction affects corporate reputation. Logistics companies can focus on the flexibility aspect of SCDM to adapt quickly to changes in demand or supply activities. In strengthening customer satisfaction, logistics companies need to emphasize the communication aspect, especially in ensuring the effectiveness of communication with consumers so that the level of customer satisfaction can be maintained and even improved. Reputation logistics companies can focus on the innovation aspect by utilizing advanced technologies such as artificial intelligence and automation to improve the efficiency and accuracy of overall supply chain management.